2016
DOI: 10.3389/fphys.2016.00261
|View full text |Cite
|
Sign up to set email alerts
|

Sickness Behavior in Honey Bees

Abstract: During an infection, animals suffer several changes in their normal physiology and behavior which may include lethargy, appetite loss, and reduction in grooming and general movements. This set of alterations is known as sickness behavior and although it has been extensively believed to be orchestrated primarily by the immune system, a relevant role for the central nervous system has also been established. The aim of the present work is to develop a simple animal model to allow studying how the immune and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Support for the adaptive nature of these ‘sickness behaviours’ has come mainly from vertebrate species challenged with deactivated pathogens or their derived components, which are sufficient to stimulate an immune response without causing pathology (Adelman & Martin, ; Lopes et al ., ). In addition to vertebrates, sickness behaviours including lethargy and anorexia have also been described in insect hosts (Ayres & Schneider, ; Kazlauskas et al ., ; Sullivan et al ., ). However, in the current experiment it is not possible to disentangle the effect of an adaptive sickness behaviour from the direct effect of pathology caused by replicating DCV.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the adaptive nature of these ‘sickness behaviours’ has come mainly from vertebrate species challenged with deactivated pathogens or their derived components, which are sufficient to stimulate an immune response without causing pathology (Adelman & Martin, ; Lopes et al ., ). In addition to vertebrates, sickness behaviours including lethargy and anorexia have also been described in insect hosts (Ayres & Schneider, ; Kazlauskas et al ., ; Sullivan et al ., ). However, in the current experiment it is not possible to disentangle the effect of an adaptive sickness behaviour from the direct effect of pathology caused by replicating DCV.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Hart 81 first argued that sickness behaviour is not a maladaptive response to infection but rather a coordinated behavioural strategy to promote host survival. A more recent hypothesis attributes sickness behaviour to altruism and kin selection 82 ; that is, sickness behaviour provides an evolutionary advantage to survival of the herd 83,84 . Interestingly, it has been reported that, if the infected host does not elicit overt sickness behaviour, they may increase their propensity to aggregate 85 .…”
Section: A Virus-versus-host Competitionmentioning
confidence: 99%
“…These phenotypes grouped under the term ‘behavioral immunity’ (de Roode and Lefèvre, 2012) or ‘sickness behavior’ (Hart, 1988) refer to a suite of neuronal mechanisms that allow organisms to detect the potential presence of disease-causing agents and to engage in behaviors which prevent contact with the invaders or reduce the consequences of the infection. Although such microbe-induced behavioral changes have been reported in Lepidoptera and Orthoptera, deciphering the molecular mechanisms involved is experimentally challenging in these insects (Sullivan et al, 2016; Kazlauskas et al, 2016; Adamo et al, 2007; Adamo, 2005). Indeed, such an analysis requires a model organism with genetic tools allowing the manipulation of actors and regulators of both the immune and neuronal systems.…”
Section: Introductionmentioning
confidence: 99%